Interferon-gamma activated calcium influx in peripheral blood lymphocytes from patients with primary and secondary progressive multiple sclerosis. Issue 5 (November 1996) - Martino, G; Brambilla, E; Filippi, M; Martinelli, V; Colombo, B; Rodegher, M; Comi, G; Grimaldi, L M
Abstract : Interferon-gamma (IFN-gamma) contributes to the early events leading to T cell activation in relapsing-remitting (RR) multiple sclerosis (MS) by activating a transplasmalemma calcium influx, the detection of which is closely associated with clinical and MRI evidence of disease activity. The appearance of this influx represents one of the earliest peripheral events in the pathogenesis of RRMS. It is still questioned whether the same immune mediated mechanisms also operate in primary progressive (PP)MS. Fluorimetric evidence of the IFN-gamma activated calcium influx was sought in 16 patients with PPMS and 39 patients with secondary progressive (SP)MS. To compare peripheral versus CNS evidence of immune activation 11 of the patients with PPMS and 27 of the patients with SPMS underwent gadolinium enhanced brain MRI. The IFN-gamma activated influx was detected in peripheral blood lymphocytes from eight of 16 (50%) patients with PPMS, and 20 of 39 (51%) patients with SPMS, a frequency similar to that previously reported in patients with RRMS during phases of disease stability. Gadolinium enhancing brain MRI lesions were found in only one of 11 (9%) patients with PPMS and 12 of 27 (41%) with SPMS. Our study shows that peripheral blood lymphocytes from patients with PPMS and patients with SPMS express with the same frequency as patients with RRMS, an IFN-gamma dependent intracellular process leading to T cell activation able to trigger disease activity.